PENGARUH PENDEKATAN PSIKOTERAPI ISLAMI DALAM DAKWAH TERHADAP KETENANGAN JIWA MAD’U - alkussaeri, Faridz; rohanah, Siti; adi ningsih, Yeni; nur failuzi, Vini dwi; rahma eka putri, Nadya (Jurnal Ilmu Pendidikan Islam, 2025)
The purpose of this study is to examine or analyze Islamic psychotherapy in influencing the mental health of the mad'u in the contemporary era. The findings of this study indicate an increase in facilitating the mad'u to accept Islamic psychotherapy material in da'wah based on modern psychological concepts. This can increase the mental peace of the mad'u for worship practices and spiritual approaches. Through a qualitative approach by applying the literature review method or a review of literature that studies Islamic psychotherapy also shows that the practice of muhasabah, dhikr, and Islamic counseling can reduce anxiety, strengthen faith, and increase emotional stability The findings of this study indicate that the practice of Islamic psychotherapy is more effective, namely showing that spiritual guidance and Islamic psychotherapy techniques can reduce psychological stress and increase mental peace. This study concludes that the Islamic psychotherapy approach remains relevant in the contemporary era.